Application of Time Series for Palm Oil Production Prediction at PT. Dwie Warna Karya : PENERAPAN TIME SERIES UNTUK PREDIKSI PRODUKSI MINYAK KELAPA SAWIT DI PT. DWIE WARNA KARYA - Putri, Elsa Monica; Hardita, Veny Cahya; Elmayantie, Catharina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Fluctuations in palm oil production at PT. Dwie Warna Karya negatively impact the company's efficiency and profitability. This study aims to implement the Time Series method using the SARIMA model to accurately predict palm oil production, enabling the company to make better decisions in production planning and operations. This research employs a quantitative approach with descriptive and predictive analysis, utilizing data collected through interviews, literature studies, and historical production documentation. The SARIMA (1,1,1)(1,1,1)12_12 model is identified as the most suitable for forecasting palm oil production over the next 12 months. The model indicates that production is influenced by previous values, requires first-order differencing to address trends, and includes a random component affected by prior forecasting errors, both in the short-term and seasonal patterns. This SARIMA model enhances forecasting accuracy and serves as a valuable reference for production planning, inventory management, and strategic decision-making.